A study of customer service rendered by Container Haulage, Kontena National, (Port Klang) / Hazlinda Hashim - Hashim, Hazlinda (Faculty of Business and Management, 1994)
The main objective of this exercise is to study the customers service level provided by Container Haulage, Kontena Nasional Port Klang and to suggest any improvements if necessary. Besides that, the research is carry out in order to study the effect of customer service on the performance and efficiency of KN haulage activities. Data is gathered through surveys, personal interviews and from published materials. It is found that the services provided by the company is at satisfactory, even thogh there are areas for improvement. It is recommended that the company should practise Electronic Data Interchange (EDI) thoroughly. Besides, appropriate training should be given to the staff and attempt should be made to improve the trailer's turnaround time.